PENINGKATAN HASIL BELAJAR BIOLOGI POKOK BAHASAN EKOSISTEM MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Sitompul, LIsnawati (FORUM PAEDAGOGIK, 2014)
AbstractThe result of studentsâ€™ learning biology in grade X-U 5 MAN 2 Padangsidimpuan havenâ€™t gratified yet. From the experience of the researcher, students always feel difficult in comprehending of ecosystem material. This is caused by using method that is not related. This research has aim to improve studentsâ€™ biology mastery through STAD Strategy. It is specified in ecosystem material. Formulation of the problem of this research is â€œto what extend STAD strategy can improve studentsâ€™ biology mastery at grade X-U 5 MAN 2 Padangsidimpuanâ€. The kind of this research is action class room research (CAR) with two cycle. In each cycle consist of four step; planning, action, observation, and reflection. Informant of this research is students in X-U 5 grade with total of students are twenty five students. Data in this research is collecting through observation, interview, and test. Technique of collecting data use descriptive analysis.The result of this research shows that STAD strategy in ecosystem material can improve studentsâ€™ biology mastery in X-U 5 grade of MAN 2 Padngsidimpuan. The mean of the studentsâ€™ biology result can get 83,69 and percentage of students can get standardized in 88% from KKM.Key Word: STAD Strategy, result of learning.